IMPROVING THE STUDENTS' VOCABULARY MASTERY THROUGH INQUIRY- BASED TEACHING (A CLASSROOM ACTION RESEARCH AT THE FOURTH YEAR OF SD NEGERI NGABEAN 3 KARTASURA IN 2009/ 2010 ACADEMIC YEAR) - ARVIANAWATI, SEPTINA HAPSARI (2011)
The general objective of this research is to improve the student's vocabulary. It was conducted because some problems were found in the classroom, namely (1) the students get difficulties in pronouncing words correctly, (2) the student's attention and motivation in learning vocabulary are decreasing. The problems are caused by (1) the limited time, so that the teacher didn't give enough time for the student to practice the vocabulary, (2) the teacher's capability in managing the class In achieving the objectives of the research, the researcher uses Classroom Action Research (CAR). This classroom action research was conducted in two cycles. There are two cycles in this action research in which each cycle is conducted in two meetings. Each cycle consisted of four steps, namely planning, action, observation and reflection. The research was held in SD Negeri Ngabean 3 Kartasura at the fourth year that consists of 25 students. In collecting the data, the writer used observation, interview and test. The result of the research shows that inquiry-based teaching can improve the students' vocabulary mastery. It also improved the students' participation in learning vocabulary. The students were more active in the process of teaching vocabulary. They are also very enthusiastic, braver and more confident in practicing English. In addition, their vocabulary mean score in the first cycle that was 62 .40 and improved to 81 .20 in the second cycle.